2021
DOI: 10.1155/2021/3135043
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Pinggan Yiqi Yangshen Recipe Combined with Labetalol Hydrochloride and Magnesium Sulfate in the Treatment of PIH

Abstract: Background. To observe the clinical effect of Pinggan Yiqi Yangshen recipe combined with labetalol hydrochloride and magnesium sulfate in the treatment of pregnancy-induced hypertension (PIH). Methods. A total of 126 patients with PIH diagnosed in our hospital from January 2016 to May 2018 were randomly divided into the control group and the experimental group, with 63 cases in each group. The control group was treated with labetalol combined with magnesium sulfate. On the basis of the control group, the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Studies suggested that the exclusive treatment of magnesium sulfate to treat pregnancy-induced hypertension (PIH) will affect fetal development ( Pascoal et al, 2019 ). Li et al ( Li et al, 2021 ) discussed the use of magnesium sulfate in combination with labetalol, which proved its efficacy in improving delivery outcomes and maternal and fetal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested that the exclusive treatment of magnesium sulfate to treat pregnancy-induced hypertension (PIH) will affect fetal development ( Pascoal et al, 2019 ). Li et al ( Li et al, 2021 ) discussed the use of magnesium sulfate in combination with labetalol, which proved its efficacy in improving delivery outcomes and maternal and fetal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to improve the antihypertensive effect and improve the delivery outcome, clinical treatment should actively explore effective means. Li et al [ 21 ] believed that the combination of magnesium sulfate and labetalol had an obvious therapeutic effect on PIH, which could effectively improve the delivery outcome and prognosis. This is similar to the result of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Not only can PE cause heart, liver, brain, and kidney failure, but it can also lead to premature abortion or stillbirth (Hsieh-Lo et al 2020). If GH cannot be controlled timely and effectively, it is easy to develop into severe PE, which is a serious threat to the life safety of both the pregnant women and the fetus (Li et al 2021).…”
Section: Accepted Manuscriptmentioning
confidence: 99%